Legal Status of Authentic Deeds Made by a Notary and Proposed to be Dishonorably Dismissed (Study of Decision Number: 200 Pk/Tun/2022) - Prasetya, Arnasteisya Putri; Bawono, Bambang Tri; Prayitno, Ahmad Hadi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze criminal violations that may serve as the basis for dishonorable dismissal of a Notary, the relationship between such violations and the administrative aspects of the notarial office, the dismissal procedure, and the legal standing of authentic deeds made by a Notary proposed for dishonorable dismissal. The research method employed is normative legal research with statutory and conceptual approaches, using literature review and documentation, and analyzed qualitatively. The findings indicate that criminal violations committed by a Notary may lead to dishonorable dismissal as they undermine the dignity of the profession and affect the administrative aspects of the notarial office. The dismissal procedure is carried out through recommendations from the Central Supervisory Council and finalized by the Minister of Law and Human Rights. Authentic deeds made by a Notary during the period of proposed dismissal remain valid and possess full evidentiary strength as long as they meet formal and material requirements, as affirmed in Supreme Court Decision No. 200 PK/TUN/2022. However, the study also reveals normative ambiguities among the Notary Office Act, Bankruptcy Act, Civil Code, and Criminal Procedure Code, which result in multiple interpretations and legal uncertainty. Therefore, reformulation and harmonization of legislation are necessary to ensure legal certainty, strengthen the integrity of the notarial profession, and protect public interests.